Techno-Humanistic Learning: A New Paradigm for Human-Centered Digital Pedagogy on Islamic Education - Achmad Maulidi; M. Zainuddin Alanshori; Zuhriyyah Hidayati; Nur Afifah Khurin Maknin; Wirdatur Rahmah; Achmad Muhibin Zuhri; Achmad Zaini (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study proposes Techno-Humanistic Learning (THL) as a new paradigm of humanistic digital pedagogy in Islamic education. Its main objective is to explore how digital learning can be implemented while maintaining a human-centred approach. Using a systematic literature review of 39 articles from international databases, the study identified three key findings. Firstly, the THL Framework presents an operational map for humanistic digital learning based on Islamic values. This includes the roles of teachers and their pedagogical attitudes, as well as technology integration. Secondly, the THL principles emphasise integrating the cognitive, affective and psychomotor domains with 21^(st)-century skills, digital ethics and universal human values. Thirdly, THL Transformation explains the shift in the teacher–student relationship towards greater collaboration and technology-based reflection, as well as the strengthening of digital literacy based on spirituality and morality. This research confirms that THL is not just a concept, but can be applied to digital Islamic education policy in Indonesia, particularly in curriculum development, strengthening teacher competencies, and humanistic digital literacy regulations. Thus, THL contributes to a new direction for Islamic education that is more inclusive, fair, human-oriented and relevant to the challenges of the digital era.